Substituting Natural Gas with Hydrogen for Thermal Application in a Hard-to-Abate Industry: A Real Case Study - Seyed Ariana Mirshokraee; Stefano Bedogni; Massimiliano Bindi; Carlo Santoro (Hydrogen, 2025)
To pursue the total decarbonization goal set at 2050, the introduction of hydrogen to replace the usage of fossil fuel in hard-to-abate industrial sectors is crucial. Hydrogen will replace natural gas in hard-to-abate sectors where natural gas is required to make heat necessary for the industrial process. Naturally, all this is worthwhile if hydrogen is produced following a green pathway, meaning that it is connected with renewable sources. In this manuscript, a techno-economic analysis related to a real case scenario is carried out. The real system addressed involves continuous high-temperature industrial furnace operation with a seasonally variable but stable thermal energy demand, representing typical conditions of hard-to-abate industrial processes. Solar photovoltaic panels combined with batteries are used to generate and store electricity that in turn is used to generate green hydrogen. Different scenarios are considered, including mixed natural gas/hydrogen, the seasonal variability of industrial needs, and the variability of solar production. The economic aspects considered include the usage of anion exchange membrane water electrolyzers (AEMWEs) to produce green hydrogen, the improvement in efficiency during operations (operational costs, OPEX), and the decrease in the AEMWE cost (Capital expenditures, CAPEX) that occur over time. The study shows that the hydrogen production cost could decrease from 12.6 EUR kg−1 in 2024 to 9.7 EUR kg−1 in 2030, with further reduction to 8.7 EUR kg−1 achievable through seasonal blending strategies. CO2 emissions are significantly reduced through partial displacement of natural gas with green hydrogen, highlighting the environmental potential of the system.